Assessment of Health Needs in Children with Congenital Upper Limb Differences in Nicaragua: Community Case Study - Canizares, Maria F.; Rios Roque, Jairo J.; Ramos Zelaya, Gabriel; James, Michelle A. (Frontiers in Public Health, 2017)
Congenital anomalies are prevalent in Nicaragua, and disability is estimated to be 10% in the general population. We studied children with congenital upper limb differences, as they are vulnerable to disability. This case study documents a collaborative effort between American and Nicaraguan orthopedic surgeons to determine unmet health needs of children with congenital upper limb differences at Hospital Manuel de Jesus Rivera (“La Mascota” Hospital) in Nicaragua, with the goal of developing programs that successfully address these needs within the context of the priorities of the community. Participants were recruited during one of the biannual pediatric hand specialty clinics held by a partnership of pediatric hand surgeons and occupational therapists under the auspices of Health Volunteers Overseas (La Brigada de las Manos, or “La Brigada”) and Nicaraguan orthopedic surgeons. Structured interviews were performed with 34 parents or caregivers of patients with the diagnosis of a congenital upper limb difference. Parents were asked to rank the social, economic, environmental, and biological factors that determine health according to priority. Using the Hanlon Method for prioritizing health problems, in consultation with local providers and the program director of La Brigada, five needs were identified: (1) improvements in access to specialized care from hand surgeons and (2) rehabilitation specialists; (3) improvements in upper extremity function; (4) access to transportation; and (5) improvement in physical activity and sports participation. Based on the results of this needs assessment, we learned that some of the needs were already part of the ongoing work of the partnership, but in addition, more needs became evident; for that reason, local health care providers and members of La Brigada identified potential solutions to these needs and are currently working to translate these in future interventions.